Genome Dynamics of Hybrid Saccharomyces cerevisiae During Vegetative and Meiotic Divisions. Issue 11 (1st November 2017) - Dutta, Abhishek; Lin, Gen; Pankajam, Ajith V; Chakraborty, Parijat; Bhat, Nahush; Steinmetz, Lars M; Nishant, Koodali T
Abstract: Mutation and recombination are the major sources of genetic diversity in all organisms. In the baker's yeast, all mutation rate estimates are in homozygous background. We determined the extent of genetic change through mutation and loss of heterozygosity (LOH) in a heterozygous Saccharomyces cerevisiae genome during successive vegetative and meiotic divisions. We measured genome-wide LOH and base mutation rates during vegetative and meiotic divisions in a hybrid (S288c/YJM789) S. cerevisiae strain. The S288c/YJM789 hybrid showed nearly complete reduction in heterozygosity within 31 generations of meioses and improved spore viability. LOH in the meiotic lines was driven primarily by the mating of spores within the tetrad. The S288c/YJM789 hybrid lines propagated vegetatively for the same duration as the meiotic lines, showed variable LOH (from 2 to 3% and up to 35%). Two of the vegetative lines with extensive LOH showed frequent and large internal LOH tracts that suggest a high frequency of recombination repair. These results suggest significant LOH can occur in the S288c/YJM789 hybrid during vegetative propagation presumably due to return to growth events. The average base substitution rates for the vegetative lines (1.82 × 10 −10 per base per division) and the meiotic lines (1.22 × 10 −10 per base per division) are the first genome-wide mutation rate estimates for a hybrid yeast. This study therefore provides a novel context for the analysis of mutation rates (especially in the context of detecting LOH during vegetative divisions), compared to previous mutation accumulation studies in yeast that used homozygous backgrounds.